Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Test - Page 578: 29



Work Step by Step

Simplify. $ \dfrac{ 3+i}{1 -2i}$ Now, $ \dfrac{ 3+i}{1 -2i} = \dfrac{ 3+i}{1 -2i} \cdot \dfrac{ 1 +2i}{1 +2i}$ or, $=\dfrac{3+6i+i+2i^2}{1-(2i)^2}$ Since, $i^2=-1$ or, $=\dfrac{3+6i+i+2(-1)}{1-4(-1)}$ Hence, $\implies\dfrac{1+7i}{5}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.